PENGEMBANGAN LKPD PEMBELAJARAN KIMIA BERBASIS PROBLEM SOLVING UNTUK MENUNJANG PEMBELAJARAN KELARUTAN DAN HASILKALI KELARUTAN DI KELAS XI SMA - Meuthia Kartika Putri; Erviyenni Erviyenni; Sri Haryati; R. Usman Rery; Susilawati Susilawati (Jurnal Pendidikan Kimia Universitas Riau, 2017)
The objective of this research was to develop the student’s activity sheet as support the implementation. This research used a research and development Research and Development (R & D) with 4-D model of development that includes Definition, Design, Develop and Disseminate. Research and development conducted in the Laboratory of the Department of Study Program of Chemistry Education PMIPA the Faculty of Teacher Training and Education University of Riau. The object of this research was the students’ activity paper based on the problem solving. The data analysis techniques used in the study was descriptive statistical analysis, by calculating the percentage of validation value. The average score of the five aspects of student’s activity sheet by validator’s team, such as the content properness, presentation, didactic, construction (linguistic) and technical (graphical) respectively has a value of eligibility 89.58%, 93.75%,90, 96.67% and 89.5%, totality score validation is 91.9% meaning the student’s activity sheet developed (LKPD Developed) is proper be use in chemistry learning.Key Words: Student Activity Sheet, Problem Solving, Ksp